PUBLIC, PIRS AND POLITICS: A CASE STUDY OF PIRI-MURIDI IN DISTRICT LAKKI MARWAT - Hikmat Ullah; Dr. Fakhar Bilal (International Journal of Contemporary Issues in Social Sciences, 2024)
Guardians of the shrines, typically familiar as Pirs, are considered a crucial part of Pakistani politics. They benefit from the huge assistance of their attendants both in the countryside and from urban areas of the country manifesting them as power players in electoral politics. However, some Pirs in the province of Khyber Pakhtunkhwa do not possess the above qualities. For instance, the Pirs of district Lakki Marwat are not very popular among the residents. They do not have an enormous number of lands and jagirs to live lavish lives like the Pirs of Punjab and Sindh do. Additionally, there is no custom of celebrating Urs of demised Pir or other rituals of the shrine in the district Lakki Marwat. Their public interaction is very less and therefore, their political influence over the common masses of district Lakki Marwat is minor. This study aims to investigate the influence of local Pirs on the politics of Lakki Marwat. This article analyzes the nexus of Pirs and Politicians in the politics of district Lakki Marwat. A qualitative research method was used. To collect the data from respondents, semi-structured and unstructured interviews were conducted while, for data analysis thematic approach was adopted.